Highly Potent GalNAc-Conjugated Tiny LNA Anti-miRNA-122 Antisense Oligonucleotides - Tsuyoshi Yamamoto; Yahiro Mukai; Fumito Wada; Chisato Terada; Yukina Kayaba; Kaho Oh; Asako Yamayoshi; Satoshi Obika; Mariko Harada-Shiba (MDPI AG, 2021)
The development of clinically relevant anti-microRNA antisense oligonucleotides (anti-miRNA ASOs) remains a major challenge. One promising configuration of anti-miRNA ASOs called "tiny LNA (tiny Locked Nucleic Acid)" is an unusually small (~8-mer), highly chemically modified anti-miRNA ASO with high activity and specificity. Within this platform, we achieved a great enhancement of the in vivo activity of miRNA-122-targeting tiny LNA by developing a series of N-acetylgalactosamine (GalNAc)-conjugated tiny LNAs. Specifically, the median effective dose (ED50) of the most potent construct, tL-5G3, was estimated to be ~12 nmol/kg, which is ~300-500 times more potent than the original unconjugated tiny LNA. Through in vivo/ex vivo imaging studies, we have confirmed that the major advantage of GalNAc over tiny LNAs can be ascribed to the improvement of their originally poor pharmacokinetics. We also showed that the GalNAc ligand should be introduced into its 5' terminus rather than its 3' end via a biolabile phosphodiester bond. This result suggests that tiny LNA can unexpectedly be recognized by endogenous nucleases and is required to be digested to liberate the parent tiny LNA at an appropriate time in the body. We believe that our strategy will pave the way for the clinical application of miRNA-targeting small ASO therapy.